2008
DOI: 10.1007/s10562-008-9535-0
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Cyclohexane with Molecular Oxygen Catalyzed by SiO2 Supported Palladium Catalysts

Abstract: The di(ethylthio)ethane palladium (A) and di(ethylthio)propane palladium (B) complexes have been immobilized on the surface of silica gel and these catalyst systems are shown to serve as effective supported Pd catalysts for cyclohexane oxidation with O 2 under solvent free condition. The supported catalyst A provides best results (overall ca. 16.2% conversion, with a selectivity of 72 or 24% for cyclohexanol or cyclohexanone, respectively, which are further promoted in the presence of 2-pyrazinecarboxylic acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…They produce free HOO • radicals and create V(IV)-species, which are confirmed by DFT calculations [33,34]. We have also obtained an enhancement effect with PCA in the oxidation (O 2 ) of alkanes, catalyzed by supported V and Pd catalysts [24,35,36].…”
Section: Co-catalyst Effectsupporting
confidence: 73%
“…They produce free HOO • radicals and create V(IV)-species, which are confirmed by DFT calculations [33,34]. We have also obtained an enhancement effect with PCA in the oxidation (O 2 ) of alkanes, catalyzed by supported V and Pd catalysts [24,35,36].…”
Section: Co-catalyst Effectsupporting
confidence: 73%
“…There might be a possible structural modification of the nano-catalyst (by TGA). It suggests that the change of colour upon use and/or the deposition of polymerized Cy-hx material on the catalyst surface, which can also act as pore-blocker of solid catalysts [23,25,32,33].…”
Section: Reaction Mechanism For Oxidationmentioning
confidence: 99%
“…15 % and 20 %, respectively [23,24]. Some mesoporous silica supported di(ethylthio)alkanes Pd catalysts have also provided 16 % conversion in the same alkane reaction [25]. A literature survey shows that not only precious metal based catalysts but also non-precious metals i.e.…”
mentioning
confidence: 99%
“…The products resulting from its partial oxidation, cyclohexanol/cyclohexanone, also called K/A-oil, are very important for the production of adipic acid, which is used in the manufacture of textile fibres, such as nylon-6 and nylon-6.6. Normally the industrial process includes several reaction steps and produces toxic chlorinated by-products [72]. Using iodosylbenzene as oxidant and Ni-clay catalysts, Mata et al [71] found a very interesting system that led to cyclohexanone as the only product, with yields ranging from 20 to 27%, and 100% selectivity, under mild conditions.…”
Section: Epoxidationmentioning
confidence: 99%